Correlation of Postoperative Imaging With MRI and Clinical Outcome After Cartilage Repair of the Ankle: A Systematic Review and Meta-analysis. Issue 2 (April 2022) - Waltenspül, Manuel; Zindel, Christoph; Altorfer, Franziska C. S.; Wirth, Stephan; Ackermann, Jakob
Background: Magnetic resonance imaging (MRI) is commonly used for evaluation of ankle cartilage repair, yet its association with clinical outcome is controversial. This study analyzes the correlation between MRI and clinical outcome after cartilage repair of the talus including bone marrow stimulation, cell-based techniques, as well as restoration with allo- or autografting. Methods: A systematic search was performed in MEDLINE, Embase, and Cochrane Collaboration. Articles were screened for correlation of MRI and clinical outcome. Guidelines of Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) were used. Chi-square test and regression analysis were performed to identify variables that determine correlation between clinical and radiologic outcome. Results: Of 2687 articles, a total of 43 studies (total 1212 cases) were included with a mean Coleman score of 57 (range, 33-70). Overall, 93% were case series, and 5% were retrospective and 2% prospective cohort studies. Associations between clinical outcome and ≥1 imaging variable were found in 21 studies (49%). Of 24 studies (56%) using the composite magnetic resonance observation of cartilage repair tissue (MOCART) score, 7 (29%) reported a correlation of the composite score with clinical outcome. Defect fill was associated with clinical outcome in 5 studies (12%), and 5 studies (50%) reported a correlation of T2 mapping and clinical outcome. Advanced age, shorter follow-up, and larger study size were associated with established correlation between clinical and radiographic outcome ( P = .021, P = .028, and P = .033). Conclusion: Interpreting MRI in prediction of clinical outcome in ankle cartilage repair remains challenging; however, it seems to hold some value in reflecting clinical outcome in patients with advanced age and/or at a shorter follow-up. Yet, further research is warranted to optimize postoperative MRI protocols and assessments allowing for a more comprehensive repair tissue evaluation, which eventually reflect clinical outcome in patients after cartilage repair of the ankle. Level of Evidence: Level III, systematic review and meta-analysis.